The mediating roles of loneliness at work and burnout in the relationship between career adaptability, organizational commitment, and job satisfaction among teachers - Kara, Ahmet; Kayışdağ, Erman; Bek, Hafız (Research Square Platform LLC, 2024)
Abstract This research examines the mediating roles of loneliness at work and burnout in the relationship between career adaptability, organizational commitment, and job satisfaction among teachers. The analysis was conducted with 256 teachers. Data were collected with the Organızatıonal Commıtment Scale, Career Adaptabilities Scale, Loneliness at Work Scale, Burnout Measure, and Job Satisfaction Scale. Data were analyzed with a two-stage structural equation modeling technique. According to the research findings, it has been proven that the mediatory effects of loneliness at work and burnout are significant in the relationship between organizational commitment and job satisfaction.
Keywords: 8. Economic growth